2013
DOI: 10.1186/1756-8722-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a high-throughput in vitro cord formation model insensitive to VEGF inhibition

Abstract: BackgroundAnti-VEGF therapy reduces tumor blood vessels, however, some vessels always remain. These VEGF insensitive vessels may help support continued tumor growth and metastases. Many in vitro assays examining multiple steps of the angiogenic process have been described, but the majority of these assays are sensitive to VEGF inhibition. There has been little focus on the development of high-throughput, in vitro assays to model the vessels that are insensitive to VEGF inhibition.MethodsHere, we describe a fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…This increase in Ang1 is likely from pericytes associated with the endothelial cells. Ang1 is secreted by pericytes and previous studies have shown that pericyte association with cords began on day 3 and increased with time [7]. Therefore, there are likely only enough pericytes present at the 96 hr time point to effectively increase the Ang1 concentration.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This increase in Ang1 is likely from pericytes associated with the endothelial cells. Ang1 is secreted by pericytes and previous studies have shown that pericyte association with cords began on day 3 and increased with time [7]. Therefore, there are likely only enough pericytes present at the 96 hr time point to effectively increase the Ang1 concentration.…”
Section: Discussionmentioning
confidence: 93%
“…This assay can be run in 96 and 384 well format with qualitative analysis on either an ArrayScan or an Acumen ([7] and Figure S2 ). Quantitative validation was performed on a similar assay ran on the Acumen eX3 in a 384 well format (Z′ score  = 0.68 or 0.70 and MSR  = 1.69 or 1.99 for tube area and SMA area analysis respectively; Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EC functional assays are useful to recapitulate one or multiple events of the angiogenesis cascade, but many existing assays lack the ability to recapitulate VEGF-dependent[5,15,62] and MMP-dependent[13,14] angiogenesis and currently lack chemically-defined substrates in a quantitative assay format relevant to angiogenesis. Therefore, there is a motivation to develop in vitro platforms in which EC behavior is dependent on VEGF signaling and MMP activity in a chemically-defined array format.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of dependence on MMP activity is a limitation of two-dimensional configurations that are commonly used in small molecule screening applications[13,14]. Furthermore, the vascular endothelial growth factor (VEGF)-dependence is unclear in some tubulogenesis assay platforms[5,15], and this further limits comparisons of EC tubulogenesis to VEGF-dependent in vivo vascular formation[1]. …”
Section: Introductionmentioning
confidence: 99%